Evaluation of bypass influence on reducing air polution in Vilnius city - Vitkūnas, Rolandas; Meidutė, Ieva (Transport, 2011)
The segment of transport is a significant part of social and economic infrastructure and has a direct impact on certain economic or social territory development. It is known that production and/or trading scale development in a specific territory leads to increased requirements for infrastructure as well as to arising environmental protection issues. Therefore, this paper addresses a very significant problem of constantly increasing vehicle numbers that decrease the permeability of roads and increase traffic jams, which consequently, have an impact on the pollution of the environment. The main goal of this paper is to evaluate bypasses and high-speed streets based on data on Vilnius City using the multi-criteria evaluation method and to verify the hypothesis of the authors.First Published Online: 12 Apr 2011